PENGARUH PENAMBAHAN LOGAM FE(II) TERHADAP LAJU PERTUMBUHAN FITOPLANKTON CHLORELLA VULGARIS DAN PORPHYRIDIUM CRUENTUM - Rizky, Yusi Anda; Suharja, Jaya; Dirga, Ayusti; Ilham, Ilham (Program Kreativitas Mahasiswa - Penelitian, 2013)
Research about the Effect of Fe(II) Addition Toward Growth rate of Phytoplankton Chlorella vulgaris and Porphyridium cruentum have been done.  It used sea water that was added by Conway medium and vitamin as culture media on the second species of phytoplankton test. Exposure of Fe (II) was conducted in culture media whose concentration were 0,0; 0,1; 0,2; 0,3; 0,4; 0,6; 0,8; 1,0; 1,5; and 2,0 ppm in order to increase the growth rate of phytoplankton. The result indicated that phytoplankton C. vulgaris is the higher cell density 3.060 x 104 cell/mL.  Maximum tolerance concentration of Fe (II) by phytoplankton C. vulgaris is   0,6 ppm and density cell is 9.612 x 104 cell/mL. Keywords: Chlorella vulgaris, Fe(II), Growth rate, Phytoplankton, Porphyridium cruentum